Grey Prediction of Mountainous Runoff of Datengxia Based on R/S Analysis - CUI Yanhua; WANG Li; WU Wenqiang (Renmin Zhujiang)
Grey prediction model has been widely used in studies on surface hydrological series,but it has not been mentioned in studies on the mountainous runoff of Datengxia.According to the annual measured data of mountainous runoff of Datengxia from 1932 to 2021,the GM (1,1) grey prediction model is established first.Then R/S analysis is carried out to calculate the Hurst index and the average cycle period T of the mountainous runoff series of Datengxia.After that,the grey prediction of the mountainous runoff of Datengxia is performed within a cycle T based on R/S-GM (1,1) model.The results show that the cycle period T of the mountainous runoff of Datengxia is nine years,and the model accuracy of GM (1,1) and R/S-GM (1,1) models is 84.38% and 87.46%,respectively,with a prediction accuracy of 86.28% and 92.54%,respectively.The grey prediction accuracy of R/S-GM (1,1) model is significantly higher than that of GM (1,1) model.This method has provided a new method for scientifically predicting the mountainous runoff of Datengxia.